Decision Support Systems: Enhancing Decision-Making with Interactive Computer-Based Systems (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Decision support systems are interactive, computer-basedsystems that aid users in judgment and choice activities. They provide datastorage and retrieval but enhance the traditional information access andretrieval functions with support for model building and model-based reasoning.They support framing, modeling, and problem solving. Typical application areasof DSSs are management and planning in business, health care, the military, andany area in which management will encounter complex decision situations.Decision support systems are typically used for strategic and tacticaldecisions faced by upper-level management decisions with a reasonably lowfrequency and high potential consequences in which the time taken for thinkingthrough and modeling the problem pays off generously in the long run.